2007
DOI: 10.1080/08958370601051677
|View full text |Cite
|
Sign up to set email alerts
|

Size-Resolved Respiratory-Tract Deposition of Fine and Ultrafine Hydrophobic and Hygroscopic Aerosol Particles During Rest and Exercise

Abstract: Airborne ultrafine particles (diameter <100 nm) are ubiquitous in the environment and have been associated with adverse health effects. The respiratory-tract deposition of these particles is fundamentally influenced by their hygroscopicity: their ability to grow by condensation of water in the humid respiratory system. Ambient particles are typically hygroscopic, to varying degrees. This article investigates the influence of hygroscopicity, exercise level, gender, and intersubject variability on size-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
127
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 196 publications
(146 citation statements)
references
References 31 publications
11
127
0
3
Order By: Relevance
“…The data showed that some subjects may have DFs that are more than twice as high as for others. This observation has also been reported in other studies (Löndahl et al, 2007).…”
Section: Lung Deposition Fractionsupporting
confidence: 92%
See 3 more Smart Citations
“…The data showed that some subjects may have DFs that are more than twice as high as for others. This observation has also been reported in other studies (Löndahl et al, 2007).…”
Section: Lung Deposition Fractionsupporting
confidence: 92%
“…There are no previous experimental studies that cover the full size range of 15-5000 nm, and very few that cover particles on both sides of the minima in the deposition curve. For particles below the minima, where diffusion is the dominating deposition mechanism, there is good agreement between the DFs here reported and those found in previous studies on healthy subjects, during spontaneous breathing of hydrophobic particles (Heyder et al, 1982;Bennett et al, 1996;Daigle et al, 2003;Chalupa et al, 2004;Wiebert et al, 2006a, b;Löndahl et al, 2007;Löndahl et al, 2012;Rissler et al, 2012), as shown in Fig. 3(b).…”
Section: Comparison Of Df With Previous Findingssupporting
confidence: 92%
See 2 more Smart Citations
“…The literature data for dry hydrophobic particles has been taken from the Multiple Part Particle Deposition (MPPD) model (version 1.0, Chemical Industry Institute of Toxicology, Research Triangle Park, NC), with inspiratory fraction of 0.5, particle density of 1000 kg/m 3 , nasal breathing, tidal volume of 0.625l, and a breathing frequency of 12 breaths per minute. The reason for choosing this model is that the respiratory deposition of sub-200 nm particle diameter resembles that of the deposition previously measured with the RESPI instrument of hydrophobic particles during spontaneous breathing (Löndahl et al, 2007). For instance the MPPD model fits better with these empirical data than the ICRP model (ICRP, 1995), which is also frequently used.…”
Section: Calculation Of the Deposited Fraction In The Respiratory Tractmentioning
confidence: 99%